The Clustering of Severe Dust Storm Occurrence in China From 1958 to 2007. Issue 15 (15th August 2018) - Guo, Li; Fan, Bihang; Zhang, Fuqing; Jin, Zhao; Lin, Henry
Abstract: China is subjected to severe dust storms that deteriorate air quality and cause substantial damages to environment and socioeconomics. Although the annual frequency of severe dust storms in China has been declining since the 1950s, the variability of severe dust storm occurrence in time and space remains inadequately described under the changing climate. Based on the continuous observation at 368 meteorological observation sites across the mainland China over a 50‐year period (1958 to 2007), we found that the temporal clustering of severe dust storm outbreak has intensified after 1985, which exacerbated the irregularity in the monthly distribution of severe dust storms. Moreover, the timing of the clustering has shown a higher interannual variation after 1985. Therefore, the variability of severe dust storm occurrence has increased significantly since the 1980s at the annual and monthly time scales. In addition, the relative probability of experiencing severe dust storms with a large influential range has risen since the 1980s. Spatially, severe dust storm outbreak has receded from spreading across the country in the 1950s to primarily affecting north and northwest China in the 2000s. These findings suggest a relatively higher risk of dust storm disaster in north and northwest China that is associated with the intensified clustering of severe dust storm activity in both time and space. Continuous studies are needed to identify the favorable synoptic system that stimulates the clustering of severe dust storm outbreak. We advocate more efforts to enhance severe dust storm prediction and warning dissemination in north and northwest China. Key Points: Temporally, the clustering of severe dust storm activity in a year has intensified after 1985 in China Spatially, severe dust storms were once documented across China in the 1950s but primarily in north and northwest China after the 2000s The relative frequency of severe dust storms with a large impact area has increased in north and northwest China